Recruitment and retention of participants in UK surgical trials: survey of key issues reported by trial staff. Issue 6 (4th October 2020) - Crocker, J. C.; Farrar, N.; Cook, J. A.; Treweek, S.; Woolfall, K.; Chant, A.; Bostock, J.; Locock, L.; Rees, S.; Olszowski, S.; Bulbulia, R.
Abstract : Background: Recruitment and retention of participants in surgical trials is challenging. Knowledge of the most common and problematic issues will aid future trial design. This study aimed to identify trial staff perspectives on the main issues affecting participant recruitment and retention in UK surgical trials. Methods: An online survey of UK surgical trial staff was performed. Respondents were asked whether or not they had experienced a range of recruitment and retention issues, and, if yes, how relatively problematic these were (no, mild, moderate or serious problem). Results: The survey was completed by 155 respondents including 60 trial managers, 53 research nurses, 20 trial methodologists and 19 chief investigators. The three most common recruitment issues were: patients preferring one treatment over another (81·5 per cent of respondents); clinicians' time constraints (78·1 per cent); and clinicians preferring one treatment over another (76·8 per cent). Seven recruitment issues were rated moderate or serious problems by a majority of respondents, the most problematic being a lack of eligible patients (60·3 per cent). The three most common retention issues were: participants forgetting to return questionnaires (81·4 per cent); participants found to be ineligible for the trial (74·3 per cent); and long follow‐up period (70·7 per cent). The most problematic retention issues, rated moderate or serious by the majority of respondents, were participants forgetting to return questionnaires (56·4 per cent) and insufficient research nurse time/funding (53·6 per cent). Conclusion: The survey identified a variety of common recruitment and retention issues, several of which were rated moderate or serious problems by the majority of participating UK surgical trial staff. Mitigation of these problems may help boost recruitment and retention in surgical trials. Abstract : An online survey of surgical trial staff was conducted to identify key issues affecting recruitment and retention of participants in UK surgical trials. Several issues were reportedly experienced by over 70 per cent of respondents. Seven recruitment and two retention issues were rated 'moderate' or 'serious' by a majority of respondents. Lack of equipoise a common theme Abstract : Antecedentes: El reclutamiento y la retención de participantes en los ensayos quirúrgicos es un desafío. Conocer los problemas más habituales y conflictivos ayudará al diseño de futuros ensayos. Este estudio tuvo como objetivo identificar la percepción de los participantes sobre cuáles son los principales problemas que afectan el reclutamiento y la retención de participantes en los ensayos quirúrgicos del Reino Unido. Métodos: Encuesta electrónica a profesionales de la salud que habían participado en ensayos quirúrgicos del Reino Unido. Se preguntó a los encuestados si habían experimentado o no algún problema en temas de reclutamiento o retención y, en caso afirmativo, qué tan conflictivos fueron (ningún problema/problema leve/moderado/grave). Resultados: Completaron la encuesta 155 participantes, de los que 60 eran directores del ensayo, 53 enfermeras de investigación, 20 metodólogos de ensayos y 19 investigadores principales. Los tres problemas más comunes en el reclutamiento fueron: pacientes que prefieren un tratamiento sobre otro (81, 5% de los encuestados), escaso tiempo de dedicación de los médicos (78, 1%) y médicos que prefieren un tratamiento sobre otro (76, 8%). La mayoría de los encuestados calificaron siete problemas de reclutamiento como "moderados" o "graves", siendo el más conflictivo la falta de pacientes elegibles (60, 3%). Los tres problemas de retención más habituales fueron: participantes que olvidaron devolver los cuestionarios (81, 4%), participantes que no fueron elegibles para el ensayo (74, 3%) y el largo período de seguimiento (70, 7%). Los problemas de retención más conflictivos, calificados como "moderados" o "graves" por la mayoría de los encuestados, fueron el olvido de los participantes para devolver los cuestionarios (56, 4%) y el escaso tiempo/financiación para la enfermera investigadora (53, 6%). Conclusión: La encuesta identificó una serie de problemas habituales en el reclutamiento y la retención de los pacientes, muchos ellos calificados como "moderados" o "graves" por la mayoría del personal involucrado en los ensayos quirúrgicos del Reino Unido. Mitigar estos problemas puede ayudar a impulsar el reclutamiento y la retención en los ensayos quirúrgicos.